2023
DOI: 10.1101/2023.10.10.561804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oligodendroglial precursors orchestrate immune network instigating early demyelination in experimental autoimmune encephalomyelitis

Qi Wang,
Taida Huang,
Zihan Zheng
et al.

Abstract: The immunomodulatory cellular network that triggers early inflammation and demyelination, the key steps in multiple sclerosis (MS) pathogenesis remains poorly characterized. Here, we demonstrate that overactivation of Wnt pathway promotes pathological transformation of oligodendrocyte precursor cells (OPCs) to replicate pathological OPCs in human MS. In mouse experimental autoimmune encephalomyelitis (EAE), pathological OPCs attract CD4+ T-helper 1 (Th1) cells into the spinal cord and brain through CC-chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(133 reference statements)
0
0
0
Order By: Relevance
“…This cytokine also attracts CD8 + T cells to MS lesions, resulting in OPC death through the activation of caspase cascades via the Fas/FasL and perforin/granzyme pathways ( 24 ) ( Figure 2 ). Furthermore, a recent study observed that OPCs, along with Th1 cells, activate a subset of macrophages, leading them to become cytotoxic and subsequently induce OPC apoptosis ( 26 ). It seems that, initiated by unknown reason, OPC-expressed CCL4 starts to attract Th1 cells, and two together further recruit macrophages.…”
Section: Multiple Role-playing In Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine also attracts CD8 + T cells to MS lesions, resulting in OPC death through the activation of caspase cascades via the Fas/FasL and perforin/granzyme pathways ( 24 ) ( Figure 2 ). Furthermore, a recent study observed that OPCs, along with Th1 cells, activate a subset of macrophages, leading them to become cytotoxic and subsequently induce OPC apoptosis ( 26 ). It seems that, initiated by unknown reason, OPC-expressed CCL4 starts to attract Th1 cells, and two together further recruit macrophages.…”
Section: Multiple Role-playing In Multiple Sclerosismentioning
confidence: 99%
“…Under pathological conditions, OPCs become hypertrophic ( 22 , 23 ) ( Figures 1B–E ) and release and/or respond to cytokines ( 17 , 24 , 25 ). In multiple sclerosis (MS), OPCs also enhance the expression of MHC I and II molecules and interact with immune cells ( 24 , 26 ). All of these studies provide strong evidence of the immune function of OPC.…”
Section: Introductionmentioning
confidence: 99%